The Implementation of Multicultural Value of Pela Gandong Local Wisdom in Education (Proceedings of the International Conference on Education, 2020)
Collective memory of the Ambon Maluku community towards the conflict occurred in1999-2003 that has awakened the value of pela gandong local wisdom owned for hundreds of yearsis very important to maintain. The function is also optimized to maintain the reconciliation of theAmbon Maluku conflict that has been achieved. The Ambon Maluku community defines pelagandong as the friendship model, fraternity system, or alliance system that was developed among allindigenous people from two or more countries even before the colonial arrived. When the Ambonconflict occurred, pela gandong became part of the conflict resolution. At present, the AmbonMaluku community has expanded the function of pela gandong to various fields including education.This study aimed to reveal the implementation of the value of pela gandong local wisdom ineducation and becoming a model of multicultural education in Maluku. This study was conducted inJanuary 2018 at SMPN 9 Ambon with 99% of Christian/Catholic students and SMPN 4 SalahutuLiang with 100% of Moslem students. The research method used was descriptive qualitative toobtain the answers of the research. The data collecting techniques were literature study, interview,and participatory observation. The results of the research showed that the implementation of thevalues of pela gandong was relevant and could be integrated as a model of multicultural education.
Keywords: Local Wisdom; Multicultural Value; Pela gandong; Ambon Conflict Reconciliation